“reduccion de la sobrerotura en el crucero 3910 del nivel 2360 de la mina “pec” de la cia. consorcio minero horizonte”. tesis - Castro Muñoz, Jose Justiniano (2016)
At Consorcio Minero Horizonte mine has been carried out preparatory and development excavations, such as the case of cruises and / or bypass. The unit costs of these are increasing due to the overbreak, which requires extra time in front of the cleaning work, transportation in the mine, transport to the surface and greater support area. The ovebreak can be decreased about 17% using controlled blasting in the crown of the blasting pattern using exsablock 7/8 "x 7" explosive cartridge. To achieve this we can use the PVC pipe technique which consists in separete by forty centimeters the explosives cartridges and spacing the holes by forty centimeters also. The results were beneficial, reducing the overbreak about 17.44%, saving 115.57 dollars, which can mean a of 40.16 US Dollars / meters. It is concluded that overbreak can be reduced by applying controlled blasting to the crown of the blasting using PVC pipes technique separating explosive cartridges.